Controle de bactérias presentes em fluido de corte utilizando biocidas naturais - Sá, Pâmela Nunes (2017)
Cutting fluids are used to aid in the machining process, with the purpose of cooling, besides promoting lubrication, reducing friction in relation to the machined part and the cutting tool, thus increasing the efficiency of the work of the factories.In the machining system, the growth of microorganisms can occur, since they use the cutting fluid as food source, thus reducing the useful life of the fluids and providing economic losses and causing damages to the health of the worker.To minimize the presence of microorganisms is used a chemical called biocide, which in high concentrations can cause health damage.The objective of this research was to evaluate the efficiency of the essential oils of Ocimum gratissimum (Alfavaca), Cymbopogon nardus (Citronella) Syzygium aromaticum (Clove) and Carapa guianensis (andiroba) as a control agent for the growth of bacteria in replacement of the biocide in the machining system.Initially, cutting fluid samples were collected in an automobile industry to quantify, isolate and characterize the bacteria (heterotrophic and potentially pathogenic) present in the cutting fluid.Following the isolated bacteria were tested for susceptibility to the different concentrations of the oils to define the minimum inhibitory concentration (MIC) and antibiogram to evaluate the resistance of the bacteria isolated to antibiotics.The contact time test of the essential oils and encapsulation of the essential oil of Citronella was carried out by means of the ionic gelation technique, which consisted of the simulation of reservoirs containing cut fluid contaminated with encapsulated oil, with oil mixed directly with the oil. Cutting fluid and reservoir containing only contaminated cutting fluid, in order to evaluate the best way of applying the oils in the machining system.Among the results obtained were 1.63x107 and 2.2x107 CFU / mL heterotrophic bacteria and 3.5x105 and 2x106 CFU / mL of potentially pathogenic bacteria in the first and second fluids collection, respectively. Six groups of bacteria were isolated, corresponding to the following species: Staphylococcus aureus, Enterobacter cloacae, Escherichia coli, Enterococcus faecalis, Proteus mirabilis and Acinetobacter spp.The bacterium that presented the highest resistance to the antibiotics tested was Acinetobacter spp and the ones with the highest sensitivity were Enterobacter cloacae (A2), Escherichia coli (A3) and Proteus mirabilis (A6). The oil of Syzygium aromaticum had the largest halo formed by the lowest concentration tested (0.25%) -11.07 mm, followed by Ocimum gratissimum with halo of 11 mm and Cymbopogon nardus 10.7 mm. In the test of contact time the shortest time reduction occurred in 1 minute for Ocimum gratissimum, 5 minutes for Syzygium aromaticum and 10 minutes Cymbopogon nardus for 4 of 6 bacterial isolates. The encapsulation test was performed with the Cymbopogon nardus oil, obtaining a significant reduction in the two forms of essential oil application.